1989
DOI: 10.1093/oxfordjournals.jbchem.a122756
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure of Hemorrhagic Protein, HR2a, Isolated from the Venom of Trimeresurus flavoviridis1

Abstract: The complete amino acid sequence and disulfide bridge location of HR2a, one of the hemorrhagic proteins isolated from the snake venom of Trimeresurus flavoviridis, have been determined by analysis of peptides derived from digests with cyanogen bromide, lysyl endopeptidase, trypsin, and Staphylococcus aureus V8 protease. Peptides were purified by gel filtration followed by reversed-phase HPLC. HR2a has the amino-terminal sequence of less than Glu-Gln-Arg- and consists of a total of 202 residues with a calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…In the induction of hemorrhage, the members of the metalloprotease/disintegrin family in hemorrhagic snake venoms each function effectively against their own respective targets; platelets are targets for disintegrins; basement membranes are targets for hemorrhagic proteinases; and fibrinogen is the target for fibrinogenases (11,12,22). In concert with these proteins, VAP1 might act on endothelial cells to induce hemorrhage.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In the induction of hemorrhage, the members of the metalloprotease/disintegrin family in hemorrhagic snake venoms each function effectively against their own respective targets; platelets are targets for disintegrins; basement membranes are targets for hemorrhagic proteinases; and fibrinogen is the target for fibrinogenases (11,12,22). In concert with these proteins, VAP1 might act on endothelial cells to induce hemorrhage.…”
Section: Figmentioning
confidence: 99%
“…Some of these polypeptides are members of the metalloprotease/disintegrin family, and various activities, such as those of hemorrhagic metalloprotease (11,12), fibrinogenase (13), prothrombin activator (14), platelet aggregation inhibitor (15), have been detected in snake venoms. It is likely that similar domain structures, such as a proprotein domain, a metalloprotease domain, a disintegrin-like domain, and a cysteine-rich domain, are conserved in the protein precursors of the members of this family.…”
mentioning
confidence: 99%
“…Comparison of Snake Venom Metalloproteinases. Ht-e (paper in press), Γ. gramineus ORF [10], HR1B [6], HR2a [5], H2-Proteinase [9], Ht-d [4], LHF-Π [7], HT-2 [8]. Residues are numbered using Ht-e as a reference.…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have shown these proteinases to be capable of hydrolyzing basement membrane components, including laminin, nidogen, fibronectin and collagen type IV [2,3]. Recently, the protein sequences for five of the hemorrhagic toxins, Ht-d (hemorrhagic toxin d or atrolysin c/d) from Crotalus atrox venom [4], HR2a (hemorrhagic protein 2a or trimerelysin II) and HR1B (hemorrhagic protein IB or trimerelysin I) from Turneresurus flavoviridis venom [5,6], LHF-II (hemorrhagic factor-II) from Lachesis muta muta venom [7] and HT-2 (hemorrhagic toxin-2) from Crotalus ruber ruber venom [8], have been determined using Edman degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Its venom is a complex mixture of proteins such as phospholipases A 2 (PLA 2 s) Kihara et al, 1992;Chijiwa et al, 2003;Yamaguchi et al, 2001;Yoshizumi et al, 1990;Liu et al, 1990;Murakami et al, 2009), metalloproteases (Takahashi and Osaka, 1970;Miyata et al, 1989), serine proteases (Deshimaru et al, 1996), C-type lectins (Atoda and Morita, 1993), vascular endothelial growth factor (VEGF) (Yamazaki et al, 2003), etc. PLA 2 s in particular are the major components of the venom and expressed only in the venom gland.…”
Section: Introductionmentioning
confidence: 99%